A110: −238(G/A) TNF polymorphism impairs outcome of breast cancer patients. Issue 1 (November 2015) - Malivanova, T.; Skoromyslova, E.; Mazurenko, N.
Abstract : Tumor necrosis factor alpha (TNF) is a multifunctional cytokine, which possesses various biologic functions depending on the type of the cells and the physiological context. TNF is synthesized by immune cells as well as malignant cells. Accordingly, TNF plays an important role in the tumor and microenvironment communication as well as systemic response to the disease. TNF gene is located at HLA class III gene locus (6p21.3) and contains several sites of single nucleotide polymorphisms in promoter, which modify TNF gene expression. G to A substitution at position −238 (rs361525) decreases TNF gene expression whereas the G to A substitution at position −308 (rs1800629) increases the expression. Studies on the possible association of these polymorphisms with various malignancies risk yielded contradictory results depending on ethnicity. Breast cancer (BC) is a multifactorial disease with clinicomorphological heterogeneity. Pathways of the main BC associated molecules (ER, PR, Her2) have crossroads with TNF signaling. The goal of the study was to identify possible TNF polymorphism effects on BC predisposition and prognosis in Russian patients. Materials and methods: DNA from 413 women with newly diagnosed BC and 226 women without oncological, autoimmune or inflammatory diseases (control group) was examined. Allelic variants of −238(G/A) TNF were determined by a RFLP-PCR, the −308(G/A) TNF polymorphism was analyzed by allele-specific PCR. Additionally Ile655Val HER2 polymorphism was tested by RFLP-PCR in142 BC patients. The comparison of genotypes frequencies was performed using the Fisher's exact test. Overall survival (OS) rate of BC patients was the criterion for estimation of polymorphism prognostic significance and was analyzed by the Kaplan–Meier method. The Log-rank test was used for the comparison of different groups of patients. The difference was considered as statistically significant at p  < 0.05. Results: A minor allele −238(A) was found in 10% BC patients and in 7% women from control group. In the same way allele −308(A) was found with a close frequency in BC patients and controls (25% and 22%). It worth to note that allele A was found in two position simultaneously in <1% of persons only. So, we failed to reveal the association of both TNF polymorphisms with BC predisposition. We did not reveal genotype distribution disparities among groups with various stages of BC and the level of ER, PR and Her2 expression. While highly active allele Val655 HER2 was more frequent in BC patients with allele −238(A) then without substitution (75% and 39%, accordingly, p  < 0.05). We found that 10-year OS of BC patients was significantly lower in the presence of allele −238(A) than without it in groups possessed regional metastases (43 ± 13% and 72 ± 4%, p  < 0.005) or ER + PR + tumor(63 ± 17% and 89 ± 4%, p  < 0.02). An opposite relationship was obtained in the presence of allele −308(A) then without the substitution when the tumor size was more than 5 cm (10-year OS 69 ± 12% and 40 ± 8%, accordingly, p  < 0.05). Conclusions: This study found out the opposite effect of polymorphisms at −238 and −308 positions in TNF promoter on the outcome of BC patients. Carriers of low expressed allele −238(A) have poor outcome because of low response to standard hormone therapy which presumably connected with the activation of Her2 pathway. The obtained results allow supposing that a special approach to the treatment of this group of BC patients should be used.